Spatial and temporal variability of zooplankton off New Caledonia (Southwestern Pacific) from acoustics and net measurements. Issue 4 (11th April 2015) - Smeti, Houssem; Pagano, Marc; Menkes, Christophe; Lebourges‐Dhaussy, Anne; Hunt, Brian P. V.; Allain, Valerie; Rodier, Martine; de Boissieu, Florian; Kestenare, Elodie; Sammari, Cherif
Abstract: Spatial and temporal distribution of zooplankton off New Caledonia in the eastern Coral Sea was studied during two multidisciplinary cruises in 2011, during the cool and the hot seasons. Acoustic measurements of zooplankton were made using a shipborne acoustic Doppler current profiler (S‐ADCP), a scientific echosounder and a Tracor acoustic profiling system (TAPS). Relative backscatter from ADCP was converted to biomass estimates using zooplankton weights from net‐samples collected during the cruises. Zooplankton biomass was estimated using four methods: weighing, digital imaging (ZooScan), ADCP and TAPS. Significant correlations were found between the different biomass estimators and between the backscatters of the ADCP and the echosounder. There was a consistent diel pattern in ADCP derived biomass and echosounder backscatter resulting from the diel vertical migration (DVM) of zooplankton. Higher DVM amplitudes were associated with higher abundance of small zooplankton and cold waters to the south of the study area, while lower DVM amplitudes in the north were associated with warmer waters and higher abundance of large organisms. Zooplankton was largely dominated by copepods (71–73%) among which calanoids prevailed (40–42%), with Paracalanus spp. as the dominant species (16–17%). Overall, zooplankton exhibited low abundance and biomass (mean night dry biomass of 4.7 ± 2.2 mg m 3 during the cool season and 2.4 ± 0.4 mg m 3 during the hot season) but high richness and diversity (Shannon index ∼4). Substantially enhanced biomass and abundance appeared to be episodically associated with mesoscale features contributing to shape a rather patchy zooplankton distribution. Key Points: Acoustic measurements of zooplankton from an ADCP, an echosounder and a TAPS Zooplankton migration and composition are linked to water mass temperatures Mesoscale eddies and fronts can substantially enhance zooplankton biomass